Orbital Myositis as a Rare Extra-Intestinal Manifestation of Ulcerative Colitis - Pestana, Madalena; Mota Dória, Hugo; Gregório, Tatiana; Madureira, Ana Margarida; Abreu, Nélia (Acta Médica Portuguesa, 2026)
n/a.